A New Microstructure Development Model for the Evaluation of Concrete Setting Time - Ho-Jin Cho; Joo-Won Kang; Yong Han Ahn; Sunkook Kim; Xiao-Yong Wang (Advances in Materials Science and Engineering)
Concrete is an exceptionally attractive construction material, with stable material supply, adequate fire resistance, and high durability. Its plasticity can be both an advantage and a disadvantage from an engineering point of view, providing versatile shapes via casting and hardening but also requiring a relatively long period of time to reach its design strength. The setting time, or hardening period, needed before the freshly poured concrete can carry a load, which begins once the hydration reaction has commenced, is a key parameter for durability since it directly affects cracking resistance in early-aged concrete. The new analysis technique for calculating setting time that was developed for this study utilizes both percolation theory and the strength development model. To verify the analytical results obtained using the new model, a critical volume ratio of hydrates was determined and a series of final setting times in concrete were experimentally investigated for different temperatures, mineral admixtures (FA: fly ash; GGBFS: ground granulated blast furnace slag), and a chemical admixture (superplasticizer). The results were found to be in good agreement with the model predictions, confirming its potential utility.